Smart Laboratory Using Radio Frequency Identification (RFID) Based on The Internet of Things - Firmansyah M S Nursuwars; Reza Fragaria Audika; Sutisna Sutisna; Imam Taufiqurrahman (Journal of Computer Engineering, Electronics and Information Technology, 2022)
In Indonesia, traditional methods are still commonly used for managing laboratories. This has resulted in various issues, such as the loss of keys, and has hindered the efficiency of these laboratories. However, the integration of technology has the potential to improve laboratory management by up to 33%. A modernized laboratory system, known as an "Innovative Laboratory", combines technology with traditional management techniques. The proposed Internet of Things-based tool aims to assist laboratories in improving their management services, including a registration system, a locker system, and a desk system. This tool utilizes a Keypad 4x4 and PCF8574 to select desks and lockers, Node MCU as a microcontroller to publish identification data from an MQTT broker, and RFID technology to access and activate electronic locks and sockets. To ensure that data is successfully transferred and the selected locker and desk are available, the system requires a certain delivery time for a maximum of 251 bytes of data that can be sent at different signal strengths. Only registered users with valid identification are able to access the locker and desk systems, and users must unregister before switching to a new locker or desk. The goal of this system is to streamline and improve the management of laboratories.